(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
This article examines the critical function of translation in advertising, focusing on how it can be used to improve communication efficacy in international marketing efforts, ensure brand consistency, and bridge cultural gaps. The study highlights the significance of cultural relevance, brand consistency, market expansion, cultural sensitivity, and creative adaptability in developing effective multilingual advertising strategies by looking at the complex process of translating advertising content. This research provides important insights into how linguistic and cultural factors affect consumer perceptions, brand engagement, and market penetration in the ever-changing field of international advertising through a thorough examination of the function of translation in advertising.